2016
DOI: 10.3390/ijgi5100182
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-Based Pedestrian’s Avoidance Behavior Recognition towards Opportunistic Road Anomaly Detection

Abstract: Abstract:Road anomalies, such as cracks, pits and puddles, have generally been identified by citizen reports made by e-mail or telephone; however, it is difficult for administrative entities to locate the anomaly for repair. An advanced smartphone-based solution that sends text and/or image reports with location information is not a long-lasting solution, because it depends on people's active reporting. In this article, we show an opportunistic sensing-based system that uses a smartphone for road anomaly detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In addition to calculating these features in an entire segment, we split the segment into two parts at the second local minimum in the segment, and the statistical features are calculated from the first half (FH) and second half (SH) of the segment and the entire (ALL) segment based on the findings in Ref. 18. The second local minimum was chosen as the split point due to our observation that FH and SH tend to represent the first and second strokes of two-stroke gestures, respectively, such as "4" and "X".…”
Section: Feature Calculationmentioning
confidence: 99%
“…In addition to calculating these features in an entire segment, we split the segment into two parts at the second local minimum in the segment, and the statistical features are calculated from the first half (FH) and second half (SH) of the segment and the entire (ALL) segment based on the findings in Ref. 18. The second local minimum was chosen as the split point due to our observation that FH and SH tend to represent the first and second strokes of two-stroke gestures, respectively, such as "4" and "X".…”
Section: Feature Calculationmentioning
confidence: 99%
“…Three papers on ITS are as follows: (1) "Vehicle positioning and speed estimation based on cellular network signals for urban roads," by Lai and Kuo [41]; (2) "A method for traffic congestion clustering judgment based on grey relational analysis," by Zhang et al [42]; and (3) "Smartphone-based pedestrian's avoidance behavior recognition towards opportunistic road anomaly detection," by Ishikawa and Fujinami [43].…”
Section: Intelligent Transportation Systemsmentioning
confidence: 99%
“…Ishikawa and Fujinami from Japan in "Smartphone-based pedestrian's avoidance behavior recognition towards opportunistic road anomaly detection" used a random forest method as the classifier to analyze the azimuth patterns from smartphones for the detection of pedestrians' avoidance behaviors, and the road anomalies can be detected in accordance with the pedestrians' avoidance behaviors. In experimental environments, the practical pedestrians' avoidance behaviors were collected from 7 males and 2 females to evaluate the proposed method, and the results showed that the average accuracy of the proposed method was higher than that of other methods [43].…”
Section: Intelligent Transportation Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…as software. Various sensors are embedded into the device, which allows the a system to extract a user's and/or a device's context such as engaging activity [19], [23], [26] and a person/device location [16], [24], identity of pedestrian [28], environmental conditions around a user [8], [10], [15], [27], and so on, which contributes to provide appropriate information/services to a user based on the context. According to a phone carrying survey, 17% of people determine the position of storing a mobile phone based on contextual restrictions, e.g.…”
Section: Introductionmentioning
confidence: 99%